2014
DOI: 10.1038/hr.2014.53
|View full text |Cite
|
Sign up to set email alerts
|

The dipeptidyl peptidase-4 inhibitor teneligliptin improved endothelial dysfunction and insulin resistance in the SHR/NDmcr-cp rat model of metabolic syndrome

Abstract: Diabetes mellitus, hypertension and metabolic syndrome are major risk factors for the occurrence of cardiovascular events. In this study, we used spontaneous hypertensive rat (SHR)/NDmcr-cp (cp/cp) (SHRcp) rats as a model for metabolic syndrome to examine the effects of dipeptidyl peptidase (DPP)-4 inhibition on hypertension, glucose metabolism and endothelial dysfunction. First, we confirmed that SHRcp rats showed very severe obesity, hypertension and endothelial dysfunction phenotypes from 14 to 54 weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…However, in the present study, long-term treatment with STG in conditionally obese mice paradoxically suppressed chemokines associated with obesity. Since it has been reported that the administration of SPP-4 inhibitor improved insulin resistance and lipid metabolism (31,32), it was hypothesized that the long term administration of STG improved the metabolic status of mice fed a HFD, and as a result the expression of these chemokines was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, long-term treatment with STG in conditionally obese mice paradoxically suppressed chemokines associated with obesity. Since it has been reported that the administration of SPP-4 inhibitor improved insulin resistance and lipid metabolism (31,32), it was hypothesized that the long term administration of STG improved the metabolic status of mice fed a HFD, and as a result the expression of these chemokines was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Nakagami et al previously demonstrated using a spontaneously hypertensive corpulent congenic (SHR)/NDmcr-cp rat model that DPP-4 inhibitors improved endothelial function [38]. This rat model, a spontaneously hypertensive strain with a nonsense mutation in the leptin receptor, shows obesity, severe hypertension, insulin resistance, hyperglycaemia, increased levels of inflammatory cytokines and hyperlipidaemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, their involvement in insulin resistance (or sensitivity), another hallmark for blood glucose regulatory mechanism, remains elusive. Very recently, teneligliptin, a chemotype prolylthiazolidine-based novel DPP-4 inhibitor [3][4][5][6][7][8], was preliminarily shown to reduce insulin resistance in patients with type 2 diabetes mellitus (T2DM) [9,10] and in an animal model [11].…”
Section: Introductionmentioning
confidence: 99%